Indian Parliament - Chand, Phul (ed.); Chunkath, A. (ed.) (New Delhi, 1984)
This book cover following topics Evolution of Indian Parliament, General principles of parliamentary procedure, press and privileges of Parliament and Indian parliament and the president. .
Keywords: Cabinet system - India